(untitled) (Al-Mostansiriyah journal for Arab and international studies, 2025)
The military coups in Syria (1950-1954) marked a critical and pivotal stage in Syria’s modern history. The political reasons behind the economic collapse were considered, and this, in turn, opened the door to further coups. This era demonstrated that economic stability is impossible to achieve without a political settlement that regulates the role of the army and rebuilds trust between state and society. It also revealed that foreign interventions—despite their pivotal role—were merely an accelerating factor for accumulating internal crises, which necessitates reading this period as a warning against neglecting institutional building in transitional societies. The recurrence of coups led to the return of the parliamentary system to the political arena, divided between the Ba’ath communists, nationalists, and liberals. This negatively impacted the management of the national economy. Productive sectors, particularly agriculture and industry, were affected by the volatility of government decisions and the instability of power. Conflicts between political factions paralyzed the economic planning process. Private investment declined due to a lack of confidence in the stability of the situation, while military interventions in economic affairs increased. Domestic and foreign investments also declined due to insecurity and weak confidence in institutions. Keywords: military coups, economic repercussions, political impact.